Penguatan Akidah Islam sebagai Upaya Preventif terhadap Radikalisme Keagamaan - Ansorul Alim; Mahmud Arif (STIKes Ibnu Sina Ajibarang, 2026)
This article examines the urgency of strengthening Islamic creed (aqidah) as a preventive instrument in addressing religious radicalism. The rise of extremism is not merely driven by sociological factors, but is also rooted in a theological crisis, namely textual interpretations that give rise to exclusivism and takfiri doctrines. Employing a conceptual literature review method, this study deconstructs the pathology of radicalism and reconstructs the preventive dimensions of aqidah. The findings reveal that ideological mitigation is grounded in three dimensions of aqidah: Tawhid as a means of liberating reason from group arrogance, wasathiyyah (moderation) in maintaining tolerance, and the absolute integration of faith with social morality. To be effective, these values must be institutionalized within Islamic education through the transformation of critical pedagogy, the strengthening of religious digital literacy, and the development of an inclusive school culture. Strengthening aqidah is therefore not merely a transfer of dogma, but the formation of a moderate worldview as a strong shield against the infiltration of radical ideologies.